Aqueous Fluoride Rapid Detection based on TBAF Desilylation by a Novel Fluorogenic 7-O-tert- butyldimethylsylyl-2-(hydroxyimino)-4-methyl-2H-chromene- 3-carbonitrile - Akumu, E. O.; Barasa, S.; Lutta, S.; Akeng’a, T. (Africa Environmental Review Journal, 2021)
This report illustrates the synthesis and properties of a novel fluoride detector also called 7-O-tert-butyldimethylsylyl-2-(hydroxyimino)-4-methyl-2H-chromene-3-carbonitrile, which emits a lavender blue fluorescence in aqueous solution when fluoride ions are present. Bk-F93 F2000 Fluorospectrophotometer (FS), MRC-UV-Vis Spectrophotometer-UV-(11S/N; UEB1011006), GC micromass spectrometer (Micromass, Wythenshawe, Waters, Inc. UK), and Bruker Avance NEO 400 MHz (TXO cryogenic probe) NMR spectrometers were used for the spectral study. MestreNova (v14.0.0) program was used to process the NMR spectra. This sensor is highly specific and sensitive to water - soluble fluoride. The findings also show that fluoride doses as minimal as 0.19 μM (3.61 x1011 mgL-1) and 8.5 µM (3.79x1010 mgL-1) in tetra-n-butylammonium fluoride (TBAF) and sodium fluoride (NaF) respectively can be reliably measured almost immediately, as shown by 2nd order rate constant of 1.4 x10 M -1min-1, in comparison to most fluoride sensors' range of 0.54 - 116M-1min-1. The synthetic compound's responsiveness as a fluoride probe in chloride, bromide, iodide, nitrate and sulfate rich water indicated no direct detection interference by any of evaluated ionic species. The quantum yield of this synthesized probe was established to be higher than the selected standard (quinine sulfphate), with values at 0.72 and 0.54 respectively. Fluoride screening with 7-O-tert-butyldimethylsylyl-2-(hydroxyimino)-4-methyl-2H-chromene-3-carbonitrile is simple and fast compared to conventional approaches that involve professional staff. As a result, the approach outlined herein is applicable and incredibly useful for assessing the quality of potable water in communities.